“The Onery Council of Scientific and Industrial Pretence”: Universities in the Early NRC’s Plans for Insdustrial Research - Enros, Philip (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1991)
AbstractThe quarrel between Queen's University and the National Research Council in 1919 provides an opportunity to look at the evolving relationship between university and government science in Canada. Although several factors were involved in the NRC's decision to press for central research laboratories, the main one was the value placed on pure research by the NRC's Chairman, A.B. Macallum.